First-phase insulin secretion: can its evaluation direct therapeutic approaches?. (April 2023) - Di Giuseppe, Gianfranco; Ciccarelli, Gea; Soldovieri, Laura; Capece, Umberto; Cefalo, Chiara M.A.; Moffa, Simona; Nista, Enrico C.; Brunetti, Michela; Cinti, Francesca; Gasbarrini, Antonio; Pontecorvi, Alfredo; Giaccari, Andrea; et al.
Highlights: β Cells can adapt to pathological metabolic conditions by implementing plasticity mechanisms to increase their mass and enhance insulin secretion, thus maintaining normal glucose levels at least in the early stages of type 2 diabetes mellitus (T2DM) natural history. In T2DM the first phase of insulin secretion is impaired. This defect directly affects the clinical manifestations of the disease, primarily causing postmeal hyperglycemia, and has an impact on long-term disease-related complications. Many studies have demonstrated the effectiveness of dietary and pharmacological strategies in improving postmeal hyperglycemia via enhancing β cell function and first-phase insulin secretion parameters in particular. Because only stimulation tests can accurately estimate early β cell secretory impairments, detecting them in daily clinical practice remains challenging. Abstract: Our work is aimed at unraveling the role of the first-phase insulin secretion in the natural history of type 2 diabetes mellitus (T2DM) and its interrelationship with insulin resistance and with β cell function and mass. Starting from pathophysiology, we investigate the impact of impaired secretion on glucose homeostasis and explore postmeal hyperglycemia as the main clinical feature, underlining its relevance in the management of the disease. We also review dietary and pharmacological approaches aimed at improving early secretory defects and restoring residual β cell function. Furthermore, we discuss possible approaches to detect early secretory defects in clinical practice. By providing a journey through human and animal data, we attempt a unification of the recent evidence in an effort to offer a new outlook on β cell secretion.